Heterogeneous interface coupled super-lubricating composite coating as well as preparation method and application thereof
By depositing a titanium transition layer, a titanium/molybdenum disulfide gradient transition layer and a copper tin sulfur/molybdenum disulfide layer on the substrate surface, and forming a heterogeneous interface coupling structure through high-temperature solid phase reaction, the superlubricated coating in the prior art is solved by solving the stability of the existing technology The problem of performance and durability enables low friction and high durability coatings in vacuum environments.
Patent Information
- Application Number
- CN202311002458.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to achieve a robust macroscopic ultralubricating coating, and superlubricating systems built with nanodiamond addition or textured matrix are prone to wear under local pressure, reducing durability.
The titanium transition layer, a titanium/molybdenum disulfide gradient transition layer and a copper tin sulfur/molybdenum disulfide layer are deposited on the substrate surface in sequence by unbalanced magnetron sputtering technology, and the Cu2SnS3 and Cu4SnS4 phases are coupled to MoS2 through high-temperature solid phase reaction. Form a heterogeneous interface coupling structure.
In a vacuum environment, the friction coefficient is as low as 0.005 and continues to operate stably, meeting the service requirements of ultra-low friction and stable lubrication of aerospace vehicles. At the same time, the preparation method is green, economical and controllable, suitable for large-scale production.
Smart Images

Figure CN119465048A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of surface lubricating coating materials, and in particular relates to a super-lubricating composite coating with heterogeneous interface coupling, and a preparation method and application thereof. Background Art
[0002] Friction and wear are considered to be important factors in energy consumption and CO2 emissions in transportation and manufacturing. According to statistics, about one-fifth of the world's energy consumption is used to overcome friction. Therefore, reducing friction to ultra-low (0.1 ≥ μ ≥ 0.01, μ: friction coefficient) and super-lubricating (μ ≤ 0.01) levels will significantly reduce energy consumption and CO2 emissions. 2 Emission. Layered molybdenum disulfide (MoS 2 ) is a well-known solid lubricant material, which is widely used in mechanical engineering. It is generally believed that MoS 2 The excellent performance of the lubricant is due to the MoS 2 The weak interaction between atomic layers makes it easy to slide. In particular, MoS 2 The friction coefficient between the layers can be reduced to 10 by non-commensurate contact -3 However, MoS 2 The superlubricity of the film is fragile and transient, and depends largely on the ultra-high vacuum experimental environment and the crystallinity of the sample. Therefore, how to achieve controllable preparation of coatings with robust macroscopic superlubricity remains a scientific and technological challenge and the key to engineering applications.
[0003] At present, based on the characteristics of multi-rough contacts and incommensurate interfaces, structural superlubrication has been extended to the macroscopic scale by adding nanodiamonds or constructing heterogeneous two-dimensional materials with layer-by-layer structures on textured substrates. However, applying extremely high local pressures on multiple pre-constructed contact points may lead to increased wear, thereby reducing the durability of these superlubrication systems. In addition, the difficulty and cost of constructing such superlubrication systems will also be detrimental to their large-scale application under actual working conditions. Summary of the invention
[0004] The main purpose of the present invention is to provide a super-lubricating composite coating with heterogeneous interface coupling and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] The embodiment of the present invention provides a super-lubricating composite coating with heterogeneous interface coupling, which includes a titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper-tin-sulfur / molybdenum disulfide layer sequentially formed on the surface of a substrate in a direction away from the substrate;
[0007] The copper-tin-sulfur / molybdenum disulfide layer is obtained by high-temperature solid-phase treatment of a copper-tin doped molybdenum disulfide layer, and contains Cu 2 S N 3 Phase, Cu 4 S N 4 Phase and (002) plane preferred layered MoS 2 , and under friction induction, the Cu 2 S N 3 Phase, Cu 4 S N 4 Phase separation and MoS 2 Coupling to form Cu 2 S N 3 / MoS 2 , Cu 4 S N 4 / MoS 2 Heterojunction interface coupling structure.
[0008] The embodiment of the present invention also provides a method for preparing a super-lubricating composite coating with heterogeneous interface coupling, which comprises:
[0009] A titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper-tin doped molybdenum disulfide layer are sequentially deposited on the substrate surface by unbalanced magnetron sputtering technology to obtain a coating structure;
[0010] The coating structure is subjected to a high temperature solid phase reaction at 400-600° C. to at least convert the copper-tin doped molybdenum disulfide layer into a copper-tin-sulfur / molybdenum disulfide layer, wherein the copper-tin-sulfur / molybdenum disulfide layer comprises Cu 2 S N 3 Phase, Cu 4 S N 4 Phase and (002) crystal plane preferred layered molybdenum disulfide, thereby producing a superlubricating composite coating.
[0011] The embodiment of the present invention also provides a super lubricating composite coating with heterogeneous interface coupling prepared by the aforementioned method.
[0012] The embodiment of the present invention also provides the use of the aforementioned super-lubricating composite coating in the field of aerospace vehicle surface protection.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The superlubricating composite coating provided by the present invention is -2 It has good friction and wear performance in the environment of Pa, the friction coefficient can be as low as 0.005 and can run stably and continuously, which can meet the service requirements of ultra-low friction and stable lubrication of aerospace vehicles;
[0015] (2) The preparation method of the superlubricating composite coating provided by the present invention is green, economical, controllable, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 The CTS / MoS prepared in Example 4 of the present invention 2 -4 Surface SEM image of superlubricating composite coating;
[0018] Figure 2 The CTS / MoS prepared in Example 4 of the present invention 2 -4 Cross-sectional SEM image of superlubricating composite coating;
[0019] Figure 3 The CTS / MoS prepared in Example 4 of the present invention 2 -4TEM microstructure of CTS phase in superlubricating composite coating;
[0020] Figure 4 The CTS / MoS prepared in Example 4 of the present invention 2 -4 Friction coefficient diagram of superlubricating composite coating in vacuum environment;
[0021] Figure 5 The CTS / MoS prepared in Example 4 of the present invention 2 -4 Superlubricating composite coating after friction CTS / MoS 2 TEM image of the heterojunction interface. DETAILED DESCRIPTION
[0022] So far, various types of MoS2 coatings have been developed at home and abroad through different preparation technologies, and the process technology and methods have a great impact on their performance. Magnetron sputtering is a green low-temperature deposition technology that can accurately control the composition, structure and thickness of the coating through process parameters. Combined with element doping or multilayer structure design, the tribological properties of MoS2 coatings can be further improved. However, its friction reduction mechanism is essentially the shear slip between the transfer film and the long-range structural ordering MoS2 layers on the wear scar surface, and it is impossible to achieve continuous and stable superlubrication.
[0023] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The main purpose is to use the unbalanced magnetron sputtering technology to simultaneously introduce Cu and Sn into the molybdenum disulfide coating, and creatively synthesize Cu in situ through high-temperature solid-phase reaction. 2 S N 3 , Cu 4 S N 4 phase, and forms Cu with MoS2 under friction induction 2 S N 3 / MoS 2 and Cu 4 S N 4 / MoS 2 Heterogeneous interface coupling enables the composite coating to achieve superlubricity on a macroscopic scale in a vacuum environment.
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Specifically, as one aspect of the technical solution of the present invention, a superlubricating composite coating includes: a titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper tin sulfur / molybdenum disulfide layer (denoted as: CTS / MoS 2 layer);
[0026] The copper-tin-sulfur / molybdenum disulfide layer is obtained by high-temperature solid-phase treatment of a copper-tin doped molybdenum disulfide layer, and contains Cu 2 S N 3 Phase, Cu 4 S N 4 Phase and (002) plane preferred layered MoS 2 , and under friction induction, the Cu 2 S N 3 Phase, Cu 4 S N 4 Phase separation and MoS 2 Coupling to form Cu 2 S N 3 / MoS 2 , Cu 4 S N 4 / MoS 2 Heterojunction interface coupling structure.
[0027] The super lubricating composite coating of the present invention forms a heterogeneous interface through the transfer film on the surface of the dual ball and the coating during the friction process. 2 S N 3 Phase, Cu 4 S N 4 Phase separation and MoS 2 Coupling formed Cu 2 S N 3 / MoS 2 , Cu 4 S N 4 / MoS 2 Heterojunction interface coupling structure.
[0028] In some embodiments, in the direction away from the substrate, the MoS 2 The content showed an increasing trend.
[0029] In some embodiments, the temperature of the high-temperature solid phase treatment is 400-600°C, the atomic content of Cu in the copper-tin doped molybdenum disulfide layer is 5-20at%, the atomic content of Sn is 5-10at%, and the atomic content ratio of Cu to Sn is 2:1 to 1:2.
[0030] In some embodiments, the MoS in the copper-tin-sulfur / molybdenum disulfide layer 2 The content is 60~80at%.
[0031] In some embodiments, the friction coefficient of the superlubricating composite coating in a vacuum environment is 0.005 to 0.01.
[0032] In some embodiments, the material of the substrate includes 1Cr18Ni9, TC4 or single crystal silicon wafer, etc., but is not limited thereto.
[0033] In some embodiments, the super lubricating composite coating has a thickness of 1.5 to 2.5 μm.
[0034] In some embodiments, the thickness of the titanium transition layer is 50-150 nm.
[0035] In some embodiments, the thickness of the titanium / molybdenum disulfide gradient transition layer is 100-200 nm.
[0036] In some embodiments, the copper-tin-sulfur / molybdenum disulfide layer has a thickness of 1.5 to 2.0 μm.
[0037] Another aspect of the embodiments of the present invention further provides a method for preparing a superlubricating composite coating, comprising:
[0038] A titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper-tin doped molybdenum disulfide layer are sequentially deposited on the substrate surface by using an unbalanced magnetron sputtering technique to obtain a coating structure;
[0039] The coating structure is subjected to a high temperature solid phase reaction at 400-600° C. to at least convert the copper-tin doped molybdenum disulfide layer into a copper-tin-sulfur / molybdenum disulfide layer, wherein the copper-tin-sulfur / molybdenum disulfide layer comprises Cu 2 S N 3 Phase, Cu 4 S N 4 Phase and (002) crystal plane preferred layered molybdenum disulfide, thereby producing a superlubricating composite coating.
[0040] In some embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using a titanium target as a cathode target material, using an inert gas as a working gas, applying a target current to the titanium target, and applying a negative bias voltage to the substrate, thereby depositing a titanium transition layer on the substrate surface, wherein the target current is 3.0 to 5.0 A, the substrate bias voltage is -50 to -100 V, the working gas flow rate is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0 × 10 -3 torr, and the deposition time is 300 to 600 s.
[0041] Furthermore, the inert gas is argon, but is not limited thereto.
[0042] In some embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using titanium target and molybdenum disulfide target as cathode target materials, using inert gas as working gas, applying target current to the titanium target and molybdenum disulfide target, and applying negative bias to the substrate, so as to deposit a titanium / molybdenum disulfide gradient transition layer on the surface of the titanium transition layer, wherein the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.4 to 2.0 A, the substrate bias is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0 × 10 -3 torr, and the deposition time is 300 to 600 s.
[0043] Furthermore, the inert gas is argon, but is not limited thereto.
[0044] In some embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using molybdenum disulfide target, copper target and tin target as cathode target materials, using inert gas as working gas, applying target current to the molybdenum disulfide target, copper target and tin target, and applying negative bias to the substrate, thereby depositing a copper-tin doped molybdenum disulfide layer on the surface of the titanium / molybdenum disulfide gradient transition layer, wherein the target current applied to the molybdenum disulfide target is 1.4-2.0A, the target current applied to the copper target is 0.4-1.0A, the target current applied to the tin target is 0.4-1.0A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, and the pressure of the reaction chamber is 1.0-3.0×10 -3 torr, and the deposition time is 3600~5400s.
[0045] Furthermore, the inert gas is argon, but is not limited thereto.
[0046] In some embodiments, the preparation method specifically includes: subjecting the copper-tin doped molybdenum disulfide layer to high temperature treatment at 400-600° C. in an inert gas atmosphere;
[0047] The heating rate used is 1-10°C / min, the high temperature treatment time is 0.5-2h, the flow rate of the inert gas is 200-350sccm, and the pressure of the reaction chamber is 750-850torr.
[0048] Furthermore, the inert gas is argon, but is not limited thereto.
[0049] In some embodiments, the material of the substrate includes 1Cr18Ni9, TC4 or a single crystal silicon wafer.
[0050] In some embodiments, the preparation method further comprises: before performing the high temperature solid phase reaction, the vacuum degree of the reaction chamber is first pumped to 5×10 -3 torr, and the inside of the reaction chamber is scrubbed.
[0051] Furthermore, the reaction chamber was evacuated to a vacuum degree of 2×10 -1 Pa, first perform argon gas purge treatment on the inside of the furnace tube 3-5 times.
[0052] In some embodiments, the preparation method further comprises: before depositing the titanium transition layer, the reaction chamber is evacuated to a predetermined vacuum degree (3×10 -5 torr or less), the substrate surface is cleaned, and then plasma etching is performed. The specific etching method is to apply a bias voltage of -400 to -500 V to the substrate, the etching substrate temperature is 100 to 150° C., and the etching time is 1200 to 1800 s.
[0053] In some more specific embodiments, the super lubricating composite coating (denoted as: CTS / MoS 2 The preparation method of super lubricating composite coating comprises:
[0054] (1) Using unbalanced magnetron sputtering technology, with a titanium target as a cathode target material, an inert gas as a working gas, applying a target current to the titanium target, and applying a negative bias voltage to the substrate, thereby depositing a titanium transition layer on the substrate surface, wherein the target current is 3.0 to 5.0 A, the substrate bias voltage is -50 to -100 V, the working gas flow rate is 12 to 16 sccm, the substrate temperature is 80 to 120°C, and the reaction chamber pressure is 1.0 to 3.0×10 -3 torr, deposition time is 300-600s;
[0055] (2) Using unbalanced magnetron sputtering technology, titanium target and molybdenum disulfide target are used as cathode target materials, inert gas is used as working gas, target current is applied to the titanium target and the molybdenum disulfide target, and negative bias voltage is applied to the substrate, so as to deposit a titanium / molybdenum disulfide gradient transition layer on the surface of the titanium transition layer, wherein the target current applied to the titanium target is gradually reduced from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target is gradually increased from 0 to 1.4 to 2.0 A, the substrate bias voltage is -50 to -70 V, the working gas flow rate is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the reaction chamber pressure is 1.0 to 3.0×10 -3 torr, deposition time is 300-600s;
[0056] (3) Using unbalanced magnetron sputtering technology, using a molybdenum disulfide target, a copper target and a tin target as cathode targets, using an inert gas as a working gas, applying a target current to the molybdenum disulfide target, the copper target and the tin target, and applying a negative bias voltage to the substrate, thereby depositing a copper-tin doped molybdenum disulfide coating on the surface of the titanium / molybdenum disulfide gradient transition layer, wherein the target current applied to the molybdenum disulfide target is 1.4 to 2.0 A, the target current applied to the copper target is 0.4 to 1.0 A, the target current applied to the tin target is 0.4 to 1.0 A, the substrate bias is -50 to -70 V, the working gas flow rate is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the reaction chamber pressure is 1.0 to 3.0 × 10 -3 torr, deposition time is 3600-5400s;
[0057] (4) The obtained coating is subjected to high temperature solid phase reaction treatment to obtain CTS / MoS 2The super-lubricating composite coating is the aforementioned super-lubricating composite coating; the temperature of the high-temperature solid phase reaction treatment is 400-600°C, the heating rate is 1-10°C / min, the working gas flow rate is 200-350sccm, the reaction chamber pressure is 750-850torr, and the insulation time is 0.5-2h.
[0058] Another aspect of the embodiments of the present invention further provides a super-lubricating composite coating with heterogeneous interface coupling obtained by the aforementioned method.
[0059] In some embodiments, in the direction away from the substrate, the MoS 2 The content showed an increasing trend.
[0060] In some embodiments, the MoS in the copper-tin-sulfur / molybdenum disulfide layer 2 The content is 60~80at%.
[0061] In some embodiments, the friction coefficient of the superlubricating composite coating in a vacuum environment is 0.005 to 0.01.
[0062] In some embodiments, the superlubricating composite coating has a thickness of 1.5 to 2.5 μm.
[0063] In some embodiments, the thickness of the titanium transition layer is 50-150 nm.
[0064] In some embodiments, the thickness of the titanium / molybdenum disulfide gradient transition layer is 100-200 nm.
[0065] In some embodiments, the copper-tin-sulfur / molybdenum disulfide layer has a thickness of 1.5 to 2.0 μm.
[0066] Another aspect of the embodiments of the present invention further provides the use of the aforementioned superlubricating composite coating with heterogeneous interface coupling in the field of aerospace vehicle surface protection.
[0067] The inventors of this case also conducted the following performance tests on the super-lubricating composite coating prepared above:
[0068] The coating thickness was tested using a scanning electron microscope, and the test results showed that the coating was 1.5 to 2.5 μm.
[0069] The friction and wear test was carried out using a CSM friction tester in a vacuum environment to analyze the tribological properties. A 9Cr18 steel ball was used as the counterpart, and a reciprocating sliding method was adopted with a frequency of 5 Hz, a track length of 5 mm, a normal load of 5 N, and a running distance of 18,000 revolutions.
[0070] In summary, through the above technical solutions, the super-lubricating composite coating provided by the present invention has good friction and wear performance in a vacuum environment, with a friction coefficient as low as 0.005 and can operate continuously and stably.
[0071] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0072] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0073] Example 1
[0074] In this embodiment, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by using unbalanced magnetron sputtering technology. 2 -1Super lubricating composite coating, mainly including the following steps:
[0075] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0076] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate the chamber until the vacuum is less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0077] (3) Preparation and deposition of CTS / MoS 2 -1 super lubricating composite coating, the cavity is filled with high-purity argon gas, and Ti target (purity is 99.99at.%), MoS 2 The target material (purity is 99.9at.%), Cu target material (purity is 99.99at.%) and Sn target material (purity is 99.99at.%) are arranged and controlled, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0078] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0079] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0080] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0081] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the copper target current was kept at 0.6 A, the tin target current was kept at 0.4 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0082] High temperature solid phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas washing, heating rate of 1 ° C / min, holding temperature of 550 ° C, holding time of 0.5 h, cooling with the furnace, to obtain CTS / MoS 2 -1Super lubricating composite coating, CTS / MoS 2 The specific composition parameters of the superlubricating composite coating sample are shown in Table 1.
[0083] After the above deposition process, CTS / MoS 2 -1Super lubricious composite coating is tested for the following structural properties:
[0084] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0085] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0086] Example 2
[0087] In this embodiment, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by using unbalanced magnetron sputtering technology. 2 -2 Super lubricating composite coating, mainly including the following steps:
[0088] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0089] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0090] (3) Preparation and deposition of CTS / MoS 2 -2 super-lubricating composite coating, high-purity argon gas is filled into the cavity, Ti target (purity is 99.99at.%), MoS2 target (purity is 99.9at.%), Cu target (purity is 99.99at.%) and Sn (purity is 99.99at.%) target material layout setting is adopted, and unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0091] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0092] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0093] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0094] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the copper target current was kept at 0.6 A, the tin target current was kept at 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0095] High temperature solid phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas washing, heating rate of 1 ° C / min, holding temperature of 550 ° C, holding time of 0.5 h, cooling with the furnace, to obtain CTS / MoS 2 -2Super lubricating composite coating, CTS / MoS 2 The specific composition parameters of the -2 superlubricating composite coating sample are shown in Table 1.
[0096] After the above deposition process, CTS / MoS 2 -2Super lubricating composite coating is tested for the following structural properties:
[0097] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0098] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0099] Example 3
[0100] In this embodiment, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by using unbalanced magnetron sputtering technology. 2 -3 Super lubricating composite coating, mainly including the following steps:
[0101] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0102] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0103] (3) Preparation and deposition of CTS / MoS 2 -3 super-lubricating composite coating, the cavity is filled with high-purity argon gas, and Ti target (purity is 99.99at.%), MoS 2 The target material (purity is 99.9at.%), Cu target material (purity is 99.99at.%) and Sn target material (purity is 99.99at.%) are arranged and controlled, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0104] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0105] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0106] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0107] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the copper target current was kept at 0.6 A, the tin target current was kept at 0.8 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0108] High temperature solid phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas washing, heating rate of 1 ° C / min, holding temperature of 550 ° C, holding time of 0.5 h, cooling with the furnace, to obtain CTS / MoS 2 -3Super lubricating composite coating, CTS / MoS 2 The specific composition parameters of the -3 superlubricating composite coating sample are shown in Table 1.
[0109] After the above deposition process, CTS / MoS 2 -3 The super-lubricating composite coating is tested for the following structural properties:
[0110] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0111] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0112] Example 4
[0113] In this embodiment, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by using unbalanced magnetron sputtering technology. 2 -4 Super lubricating composite coating, mainly including the following steps:
[0114] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0115] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0116] (3) Preparation and deposition of CTS / MoS 2 -4 super-lubricating composite coating, the cavity is filled with high-purity argon gas, and Ti target (purity is 99.99at.%), MoS 2 The target material (purity is 99.9at.%), Cu target material (purity is 99.99at.%) and Sn target material (purity is 99.99at.%) are arranged and controlled, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0117] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0118] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0119] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0120] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the copper target current was kept at 0.6 A, the tin target current was kept at 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0121] High-temperature solid-phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas purge treatment, heating to 250°C at a heating rate of 1°C / min, keeping warm for 0.5h, then heating to 550°C at a heating rate of 5°C / min, keeping warm for 0.5h, and then cooling with the furnace. 2 The specific composition parameters of the -4 superlubricating composite coating sample are shown in Table 1.
[0122] After the above deposition process, CTS / MoS2 The superlubricating composite coating is tested for the following structural properties:
[0123] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0124] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0125] The CTS / MoS prepared in this example 2 -4 The surface and cross-sectional SEM images of the superlubricating composite coating are shown in Figure 1 , Figure 2 Shown; CTS / MoS 2 -4 TEM microstructure of CTS phase in superlubricating composite coating Figure 3 As shown, CTS / MoS 2 -4 The friction coefficient of super lubricating composite coating in vacuum environment is shown in the figure Figure 4 As shown, CTS / MoS 2 -4 CTS / MoS after friction of superlubricating composite coating 2 TEM image of heterogeneous interface Figure 5 shown.
[0126] Comparative Example 1
[0127] Compared with Example 4, this comparative example is different in that there is no co-doping of Cu and Sn elements. In this comparative example, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. MoS is prepared on the substrate surface by unbalanced magnetron sputtering technology. 2 Coating mainly includes the following steps:
[0128] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0129] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0130] Preparation and deposition of MoS 2 The coating is filled with high-purity argon gas in the chamber, and Ti target (purity is 99.99at.%) and MoS 2The target material (purity is 99.9at.%) is set up and unbalanced magnetron sputtering technology is used. The specific steps are as follows:
[0131] For plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 150 °C.
[0132] The titanium target sputtering current was 5.0A, the substrate bias voltage was -70V, the working gas was Ar, the gas flow rate was 16sccm, the substrate temperature was 120℃, and the pressure was 1.3×10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0133] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -70 V, the deposition substrate temperature was 110 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0134] The sputtering current of the molybdenum disulfide target was maintained at 1.6 A and the deposition time was 5400 s until MoS 2 The coating thickness reaches 2.0μm.
[0135] High temperature annealing treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas washing treatment, the heating rate is 1℃ / min, the holding temperature is 550℃, the holding time is 0.5h, and the furnace is cooled to obtain MoS 2 Composite coating.
[0136] MoS 2 The specific composition parameters of the composite coating samples are shown in Table 1.
[0137] After the above deposition process, MoS 2 The composite coating is tested for the following structural properties:
[0138] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0139] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0140] Comparative Example 2
[0141] Compared with Example 4, this comparative example is different in that there is no high-temperature solid phase reaction process. In this comparative example, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. MoS is prepared on the substrate surface by unbalanced magnetron sputtering technology. 2 / Cu-Sn composite coating, mainly including the following steps:
[0142] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0143] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0144] Preparation and deposition of MoS 2 / Cu-Sn composite coating, the cavity is filled with high-purity argon gas, and Ti target (purity is 99.99at.%), MoS 2 The target material (purity is 99.9at.%), Cu target material (purity is 99.99at.%) and Sn target material (purity is 99.99at.%) are arranged and controlled, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0145] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0146] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0147] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0148] Keep the sputtering current of the molybdenum disulfide target at 1.6A, the copper target current at 0.6A, and the tin target current at 0.6A. The other conditions remain unchanged and the deposition time is 3600s until MoS 2The thickness of the Cu-Sn composite coating reaches 2.0 μm. 2 The specific composition parameters of the Cu-Sn composite coating samples are shown in Table 1.
[0149] After the above deposition process, MoS 2 / Cu-Sn composite coating is tested for the following structural properties:
[0150] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0151] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0152] Comparative Example 3
[0153] Compared with Example 4, this comparative example is different in that there is no titanium transition layer. In this comparative example, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by unbalanced magnetron sputtering technology. 2 -5 composite coating, mainly including the following steps:
[0154] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0155] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0156] (3) Preparation and deposition of CTS / MoS 2 -5 composite coating, high-purity argon gas is filled into the cavity, Ti target (purity is 99.99at.%), MoS2 target (purity is 99.9at.%), Cu target (purity is 99.99at.%) and Sn (purity is 99.99at.%) target material layout setting is adopted, and unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0157] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0158] The titanium target sputtering current was 3.0 A, and then gradually decreased to 0 A. At the same time, the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias voltage was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0159] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the copper target current was kept at 0.6 A, the tin target current was kept at 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0160] High-temperature solid-phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas purge treatment, heating to 250°C at a heating rate of 1°C / min, keeping warm for 0.5h, then heating to 550°C at a heating rate of 5°C / min, keeping warm for 0.5h, and then cooling with the furnace. 2 The specific composition parameters of the -5 composite coating samples are shown in Table 1.
[0161] After the above deposition process, CTS / MoS 2 -5 Composite coatings are tested for the following structural properties:
[0162] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0163] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0164] Comparative Example 4
[0165] Compared with Example 4, this comparative example is different in that there is no titanium / molybdenum disulfide gradient transition layer. In this comparative example, the substrate material is 1Cr18Ni9, TC4 or single crystal silicon wafer. CTS / MoS is prepared on the substrate surface by unbalanced magnetron sputtering technology. 2 -6 composite coating, mainly including the following steps:
[0166] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0167] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0168] (3) Preparation and deposition of CTS / MoS 2 -6 composite coating, the cavity is filled with high-purity argon gas, and Ti target (purity is 99.99at.%), MoS 2 The target material (purity is 99.9at.%), Cu target material (purity is 99.99at.%) and Sn target material (purity is 99.99at.%) are arranged and controlled, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0169] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0170] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0171] The sputtering current of the molybdenum disulfide target was 1.6 A, the copper target current was 0.6 A, the tin target current was 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-tin doped molybdenum disulfide composite coating reached 2.0 μm.
[0172] High-temperature solid-phase reaction treatment, using a multi-temperature zone tubular furnace, after 3-5 times of argon gas purge treatment, heating to 250°C at a heating rate of 1°C / min, keeping warm for 0.5h, then heating to 550°C at a heating rate of 5°C / min, keeping warm for 0.5h, and then cooling with the furnace. 2 The specific composition parameters of the -6 composite coating samples are shown in Table 1.
[0173] After the above deposition process, CTS / MoS 2 -6 Composite coatings are tested for the following structural properties:
[0174] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0175] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0176] Comparative Example 5
[0177] Compared with Example 4, this comparative example is different in that only a copper-doped molybdenum disulfide layer is used; in this comparative example, the substrate material is 1Cr18Ni9, TC4 or a single crystal silicon wafer. The MoS2 / Cu composite coating is prepared on the substrate surface by using an unbalanced magnetron sputtering technique, which mainly includes the following steps:
[0178] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0179] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate the chamber until the vacuum is less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0180] (3) Preparation and deposition of MoS2 / Cu composite coating: The cavity is filled with high-purity argon gas, and a Ti target (purity of 99.99 at.%) is used. 2 The target material (purity is 99.9at.%) and Cu target material (purity is 99.99at.%) are arranged and set, and the unbalanced magnetic magnetron sputtering technology is adopted. The specific steps are as follows:
[0181] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0182] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0183] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0184] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the current of the copper target was kept at 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the copper-doped molybdenum disulfide composite coating reached 2.0 μm.
[0185] For high-temperature solid-phase reaction treatment, a multi-temperature zone tubular furnace was used. After 3-5 times of argon gas washing, the temperature was raised to 250°C at a heating rate of 1°C / min, and the temperature was kept for 0.5h. Then, the temperature was raised to 550°C at a heating rate of 5°C / min, and the temperature was kept for 0.5h, and then the temperature was cooled with the furnace. The specific composition parameters of the MoS2 / Cu composite coating sample are shown in Table 1.
[0186] The MoS2 / Cu composite coating prepared after the above deposition treatment was subjected to the following structural performance tests:
[0187] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0188] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0189] Comparative Example 6
[0190] Compared with Example 4, this comparative example is different in that only a tin-doped molybdenum disulfide layer is used; in this comparative example, the substrate material is 1Cr18Ni9, TC4 or a single crystal silicon wafer. The MoS2 / Sn composite coating is prepared on the substrate surface by using an unbalanced magnetron sputtering technique, which mainly includes the following steps:
[0191] (1) The substrate surface is mechanically polished, the substrate material is placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.
[0192] (2) Place the cleaned substrate into an unbalanced magnetron sputtering chamber and evacuate it to a vacuum degree of less than 5×10 - 4 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.
[0193] (3) Preparation and deposition of MoS2 / Sn composite coatings. The cavity is filled with high-purity argon gas, and a Ti target (purity of 99.99 at.%) is used. MoS 2The target material (purity is 99.9at.%) and Sn (purity is 99.99at.%) target material layout and setting adopt unbalanced magnetic magnetron sputtering technology. The specific steps are as follows:
[0194] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.
[0195] The titanium target sputtering current was 3.0 A, the substrate bias voltage was -70 V, the working gas was Ar, the gas flow rate was 16 sccm, the deposition substrate temperature was 80 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 300s, and a titanium transition layer with a thickness of about 100nm is deposited on the substrate surface;
[0196] The sputtering current of the titanium target was gradually reduced to 0 A, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -50 V, the deposition substrate temperature was 100 °C, and the pressure was 1.3 × 10 - 3 torr, the deposition time is 300s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 150nm;
[0197] The sputtering current of the molybdenum disulfide target was kept at 1.6 A, the current of the tin target was kept at 0.6 A, and the other conditions remained unchanged. The deposition time was 3600 s until the total thickness of the tin-doped molybdenum disulfide composite coating reached 2.0 μm.
[0198] For high-temperature solid-phase reaction treatment, a multi-temperature zone tubular furnace was used. After 3-5 times of argon gas washing, the temperature was raised to 250°C at a heating rate of 1°C / min, and the temperature was kept for 0.5h. Then, the temperature was raised to 550°C at a heating rate of 5°C / min, and the temperature was kept for 0.5h, and then the temperature was cooled with the furnace. The specific composition parameters of the MoS2 / Sn composite coating sample are shown in Table 1.
[0199] The MoS2 / Sn composite coating prepared after the above deposition treatment was subjected to the following structural performance tests:
[0200] Structural testing: Scanning electron microscope testing was used to measure the coating thickness.
[0201] Friction and wear performance test under vacuum environment: CSM friction tester is used to perform tribological performance analysis under vacuum environment. 9Cr18 steel ball is used as the dual ball, reciprocating sliding mode is adopted, the frequency is 5Hz, the track length is 5mm, the operation is 18000 revolutions, and the normal load is 5N.
[0202] The six coatings prepared by different processes in Examples 1-4 and Comparative Examples 1-6 are named as follows: CTS / MoS 2 -1. CTS / MoS 2 -2. CTS / MoS 2 -3. CTS / MoS 2 -4. MoS 2 、MoS 2 / Cu-Sn、CTS / MoS 2 -5. CTS / MoS 2 -6. MoS 2 / Cu、MoS 2 / Sn. The content of each element is shown in Table 1 below.
[0203] Table 1: Composition parameters of six coating samples in Examples 1-4 and Comparative Examples 1-2
[0204]
[0205] The composition in Table 1 refers to the content of the outermost layer. It can be seen from Table 1 that the main component of the deposited coating is MoS 2 , meeting the requirements of lubricating functional coating.
[0206] CTS / MoS in Examples 1-4 and Comparative Examples 1-6 2 -1. CTS / MoS 2 -2. CTS / MoS 2 -3. CTS / MoS 2 -4. MoS 2 、MoS 2 / Cu-Sn、CTS / MoS 2 -5. CTS / MoS 2 -6. MoS 2 / Cu、MoS 2 The thickness and friction coefficient of the Sn / Sn coating are shown in Table 2. As shown in Table 2, the films of Examples 1-4 all have the best friction coefficient under vacuum environment, and Example 4 is the most excellent.
[0207] Table 2: Thickness and vacuum average friction coefficient of six coating samples
[0208]
[0209] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0210] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A superlubricating composite coating with heterogeneous interface coupling, characterized in that: It includes a titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper-tin-sulfur / molybdenum disulfide layer which are sequentially formed on the surface of the substrate; Among them, the copper-tin-sulfur / molybdenum disulfide layer is obtained by high-temperature solid-phase treatment of a copper-tin doped molybdenum disulfide layer, and contains Cu2SnS3 phase, Cu4SnS4 phase and layered MoS2 with preferential (002) crystal plane, and under friction induction, the Cu2SnS3 phase and Cu4SnS4 phase are coupled with MoS2 to form Cu2SnS3 / MoS2 and Cu4SnS4 / MoS2 heterogeneous interface coupling structures respectively.
2. The superlubricating composite coating with heterogeneous interface coupling according to claim 1, characterized in that: Along the direction away from the substrate, the content of MoS2 in the titanium / molybdenum disulfide gradient transition layer tends to increase.
3. The superlubricating composite coating with heterogeneous interface coupling according to claim 1, characterized in that: The temperature of the high temperature solid phase treatment is 400-600° C., the atomic content of Cu in the copper-tin doped molybdenum disulfide layer is 5-20 at%, the atomic content of Sn is 5-10 at%, and the atomic content ratio of Cu to Sn is 2:1-1:2; And / or, the content of MoS2 in the copper-tin-sulfur / molybdenum disulfide layer is 60-80at%; And / or, the friction coefficient of the superlubricating composite coating in a vacuum environment is 0.005-0.01; and / or, the material of the substrate includes 1Cr18Ni9, TC4 or a single crystal silicon wafer.
4. The superlubricating composite coating with heterogeneous interface coupling according to claim 1, characterized in that: The thickness of the superlubricating composite coating is 1.5 to 2.5 μm; and / or the thickness of the titanium transition layer is 50 to 150 nm; and / or the thickness of the titanium / molybdenum disulfide gradient transition layer is 100 to 200 nm; and / or the thickness of the copper-tin-sulfur / molybdenum disulfide layer is 1.5 to 2 μm.
5. A method for preparing a superlubricating composite coating with heterogeneous interface coupling, characterized in that: include: A titanium transition layer, a titanium / molybdenum disulfide gradient transition layer and a copper-tin doped molybdenum disulfide layer are sequentially deposited on the substrate surface by using an unbalanced magnetron sputtering technique to obtain a coating structure; The coating structure is subjected to a high temperature solid phase reaction at 400-600° C. to at least convert the copper-tin doped molybdenum disulfide layer into a copper-tin-sulfur / molybdenum disulfide layer, wherein the copper-tin-sulfur / molybdenum disulfide layer comprises a Cu2SnS3 phase, a Cu4SnS4 phase and a layered molybdenum disulfide with a preferred (002) crystal plane, thereby obtaining a superlubricating composite coating.
6. The preparation method according to claim 5, characterized in that: Specifically include: The unbalanced magnetron sputtering technology is used, with titanium target as cathode target material, inert gas as working gas, target current applied to the titanium target, and negative bias applied to the substrate, so as to deposit a titanium transition layer on the substrate surface, wherein the target current is 3.0-5.0A, the substrate bias is -50--100V, the working gas flow rate is 12-16sccm, the substrate temperature is 80-120℃, and the pressure of the reaction chamber is 1.0-3.0×10 -3 torr, deposition time is 300-600s; And / or, the preparation method specifically comprises: using unbalanced magnetron sputtering technology, using a titanium target and a molybdenum disulfide target as cathode target materials, using an inert gas as a working gas, applying a target current to the titanium target and the molybdenum disulfide target, and applying a negative bias voltage to the substrate, thereby depositing a titanium / molybdenum disulfide gradient transition layer on the surface of the titanium transition layer, wherein the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.4 to 2.0 A, the substrate bias voltage is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0×10 -3 torr, deposition time is 300-600s; And / or, the preparation method specifically comprises: using unbalanced magnetron sputtering technology, using a molybdenum disulfide target, a copper target and a tin target as cathode targets, using an inert gas as a working gas, applying a target current to the molybdenum disulfide target, the copper target and the tin target, and applying a negative bias voltage to the substrate, thereby depositing a copper-tin doped molybdenum disulfide layer on the surface of the titanium / molybdenum disulfide gradient transition layer, wherein the target current applied to the molybdenum disulfide target is 1.4 to 2.0 A, the target current applied to the copper target is 0.4 to 1.0 A, the target current applied to the tin target is 0.4 to 1.0 A, the substrate bias is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0 × 10 -3 torr, and the deposition time is 3600~5400s.
7. The preparation method according to claim 5, characterized in that: Specifically include: In an inert gas atmosphere, the coating structure is subjected to high-temperature treatment at 400-600°C; wherein the heating rate is 1-10°C / min, the high-temperature treatment time is 0.5-2h, the flow rate of the inert gas is 200-350sccm, and the pressure of the reaction chamber is 750-850torr.
8. The preparation method according to claim 5, characterized in that: Also includes: Before the high temperature solid phase reaction, the vacuum degree of the reaction chamber was evacuated to 5×10 -3 torr, and the inside of the reaction chamber is scrubbed.
9. A superlubricating composite coating having heterogeneous interface coupling prepared by the method according to any one of claims 5 to 8.
10. Use of the superlubricating composite coating with heterogeneous interface coupling according to any one of claims 1 to 4 and 9 in the field of aerospace vehicle surface protection.